Chapter 15: Artificial intelligence and social memory: towards the cyborgian remembrance of an advancing mnemo-technic - Merrill, Samuel (Edward Elgar Publishing, 2023)
In this chapter, I conceptually explore the relationship between artificial intelligence (AI) and social memory. I start by briefly outlining the idea of social memory and positioning AI systems as mnemonic technologies. Thereafter I discuss how memory has primarily been conflated with storage by AI researchers and developers before suggesting the alternative conflation of computation to remembrance to foster a more integrated and hybrid understanding of social memory in the AI era. Finally, after noting a predominantly instrumentalist concern with mnemonic technologies, and drawing on the works of Donna J. Haraway and Bernard Stiegler, I introduce the concepts of cyborgian remembrance and AI mnemotechnics to help grasp the complex relationship between AI and social memory. These concepts, I argue, can enable the decentering of human memory in ways that might better facilitate the critical analysis of the challenges and risks associated with AI's increased influence on social memory matters.